Electronic Spectral Parameters of Doped Pr(III) and Nd(III) Ions in the Saturated Solutions of Some N and O Donor Biologically Important Ligands in DMF Medium - Jain, Samata; Jain, Sushma (Asian Journal of Chemistry, 2012)
The study of interaction of biologically important compounds with Pr(III) and Nd(III) ions in the form of doped model have been discussed in the terms of electronic spectral parameters viz. Oscillator strength (P), Judd-Ofelt (Tl), Racah parameter (Ek), Slater- Condon parameter (Fk), Lande parameter (z4F), Bonding parameters (b1/2), Naphelauxetic ratio (b), per cent covalency (d), rms deviation (s) and Peacock constant (K) have been evaluated. The study infers the change in absorption spectra of doped Pr(III) and Nd(III) ion with some biologically important ligands (viz. ascorbic acid, biotin, gibberalic acid, indoleacetic acid, indole-3-butyric acid, kinetin, niacin, pyridoxine, thiamin and 4-chlorophenoxyacetic acid). The doped model involves small concentration of Pr(III) ion salt (0.0435 g) and Nd(III) ion salt (0.0438 g) in saturated solution of ligand in DMF solvent at 298 K. In this comparative study, we observed that Pr(III) shows better complexation than Nd(III) ion and the complexing efficiency of biotin ligand with Pr(III) and Nd(III) is greatest among all the ten ligands.